2010
DOI: 10.1186/1750-1164-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of breast conservation after neoadjuvant taxene based chemotherapy in locally advanced breast cancer: a Prospective Phase I trial

Abstract: Background: Neoadjuvant chemotherapy is the standard care for locally advanced breast cancer. Our study aimed at evaluating the feasibility of breast conversation surgery (BCS) after neoadjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(28 reference statements)
1
2
1
Order By: Relevance
“…Several other studies have shown a similar overall objective response of the primary tumor in patients with locally advanced breast cancer ranging from 71 to 87 %. 7,8,9 On the other hand, the present results are much higher than that reported by Yadav et al who found that only 23 % showed response to neoadjuvant chemotherapy. 10 Another study by Tamer et al in 2010 also showed much lesser overall response rates to neoadjuvant chemotherapy 54.5 %(CR 3% and PR 51.5%) and Kim et al also reported that the overall response rate to neoadjuvant chemotherapy is 60 %(CR 4 % and PR 56%) respectively.…”
Section: Discussioncontrasting
confidence: 56%
“…Several other studies have shown a similar overall objective response of the primary tumor in patients with locally advanced breast cancer ranging from 71 to 87 %. 7,8,9 On the other hand, the present results are much higher than that reported by Yadav et al who found that only 23 % showed response to neoadjuvant chemotherapy. 10 Another study by Tamer et al in 2010 also showed much lesser overall response rates to neoadjuvant chemotherapy 54.5 %(CR 3% and PR 51.5%) and Kim et al also reported that the overall response rate to neoadjuvant chemotherapy is 60 %(CR 4 % and PR 56%) respectively.…”
Section: Discussioncontrasting
confidence: 56%
“…The overall response to NACT in this study was 90% (Partial = 77% and complete = 13%). Several other studies proclaimed that NACT response to LABC is ranging from 71% to 87% [20]. Interestingly, our results were the highest from this point of view.…”
Section: Discussionsupporting
confidence: 50%
“…The idea of neoadjuvant chemotherapy has been recently applied to breast cancer treatment and studies have shown the efficacy of neoadjuvant chemotherapy in down-staging the primary tumor (1). The use of neoadjuvant chemotherapy thus allows breast conservation surgery to be performed instead of mastectomy.…”
Section: Introductionmentioning
confidence: 99%